2013
DOI: 10.1155/2013/713515
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Power Generation in Continuous Flow Microbial Fuel Cell Treating Actual Wastewater: Influence of Biocatalyst Type on Electricity Production

Abstract: Microbial fuel cells (MFCs) have the potential to simultaneously treat wastewater for reuse and to generate electricity. This study mainly considers the performance of an upflow dual-chambered MFC continuously fueled with actual domestic wastewater and alternatively biocatalyzed with aerobic activated sludge and strain of Bacillus Subtilis. The behavior of MFCs during initial biofilm growth and characterization of anodic biofilm were studied. After 45 days of continuous operation, the biofilms on the anodic el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Both gram-negative Comamonas and gram-positive Bacillus have previously been reported in microbial fuel cell communities. While the genus Comamonas has been previously enriched on both cathodic and anodic communities of microbial fuel cells (Xing et al, 2010;Ishii et al, 2012;Sun et al, 2012), the genus Bacillus has only been reported from anodic communities (Nimje et al, 2009;Ismail and Jaeel, 2013;Tang et al, 2014). Some species of these genera are capable of interacting with minerals.…”
Section: Isolation and Electrochemical Characterization Of Isolated Smentioning
confidence: 99%
“…Both gram-negative Comamonas and gram-positive Bacillus have previously been reported in microbial fuel cell communities. While the genus Comamonas has been previously enriched on both cathodic and anodic communities of microbial fuel cells (Xing et al, 2010;Ishii et al, 2012;Sun et al, 2012), the genus Bacillus has only been reported from anodic communities (Nimje et al, 2009;Ismail and Jaeel, 2013;Tang et al, 2014). Some species of these genera are capable of interacting with minerals.…”
Section: Isolation and Electrochemical Characterization Of Isolated Smentioning
confidence: 99%
“…As, the electricity generation is directly proportional to how much electron release from organic waste, there were a lower amount of electricity (highest 0.40 V and 0.19 mA) in double chamber MFC while the level of electricity generation was better (highest 5.78 V and 5.03 mA) when used multiple chamber MFCs for the oxidation of organic wastes by endogenous microbes of wastewater samples. In this study, the potential bacterial strains (HWWA-1 C17 and HWWA-1 C19) are capable for producing ~0.90V and ~0.50 mA respectively which was better than previous studies [24][25][26][27].…”
Section: Discussionmentioning
confidence: 63%
“…Two other important CEMs that have been used in METs recently include Ultrex CMI 7000 made by Membranes Inc. USA) and Hyflon Ion made by Solvay-Solexis SPA. Ultrex CMI 7000 is a strong, acid polymer membrane with a gel polystyrene backbone structure cross-linked with divinyl benzene containing a large amount of sulphonate groups (Ismail and Jaeel, 2013). Although its cation conductivity and mechanical durability are comparable to Nafion, its performance in MFCs is poorer than Nafion (Sotres et al, 2014) because its ohmic resistance is quite high (Rahimnejad et al, 2014b).…”
Section: 113mentioning
confidence: 99%